2008
DOI: 10.1021/ja8031955
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Rhodium Carboxamidate Catalyst for Enantioselective C−H Amination

Abstract: Catalytic intramolecular C-H amination has advanced as a general technology for chemical synthesis. 1 The utility of the heterocyclic products fashioned from such processes validates efforts to identify chiral transition-metal complexes capable of effecting asymmetric insertion (Figure 1). On a more fundamental level, the challenges associated with the design of a catalytic system able to support a reactive oxidant that can discriminate between two hydrogen atoms on a prochiral methylene center are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(108 citation statements)
references
References 24 publications
2
104
0
2
Order By: Relevance
“…This is exemplified by reports from the groups of Che, [198] Davis, [199] and Du Bois. [200] Ah ighly enantioselective asymmetric intramolecular nitrene transfer to unactivated C(sp 3 ) À Hb onds remains to be developed. Similar to transition-metal catalysis,b ut in contrast to radical reactions,the cyclic transition state for intramolecular carbene/nitrene transfer provides an opportunity for ap reexisting stereogenic center to communicate effectively with aforming one.T hus,ahigh level of diastereomeric control is sometimes observed.…”
Section: Transfer Of Carbenes/nitrenesmentioning
confidence: 99%
“…This is exemplified by reports from the groups of Che, [198] Davis, [199] and Du Bois. [200] Ah ighly enantioselective asymmetric intramolecular nitrene transfer to unactivated C(sp 3 ) À Hb onds remains to be developed. Similar to transition-metal catalysis,b ut in contrast to radical reactions,the cyclic transition state for intramolecular carbene/nitrene transfer provides an opportunity for ap reexisting stereogenic center to communicate effectively with aforming one.T hus,ahigh level of diastereomeric control is sometimes observed.…”
Section: Transfer Of Carbenes/nitrenesmentioning
confidence: 99%
“…[90] Kürzlich wurde auch über eine enantioselektive Nitreninsertion als vielversprechende asymmetrische C-H-Aminierungsmethode berichtet. [91] Trotz aller Erfolge bei der Entwicklung der Pd-katalysierten asymmetrischen Katalyse erbrachten die Studien zur enantioselektiven Funktionalisierung von C-H-Bindungen über eine Pd-Insertion bislang kaum positive Ergebnisse. [92][93][94][95] Es scheint, dass vor allem zwei Probleme die Weiterent- -katalysierten C-H-Aktivierung/C-C-Kupplung erzielen konnten, nahmen wir uns vor, enantioselektive Varianten dieser Reaktionen zu entwickeln (Schema 57).…”
Section: Enantioselektive C-h-aktivierung/c-c-kupplungunclassified
“…In the rhodium case, some authors have proposed the concerted pathway, although not all the experimental evidences are in complete accord with this. For instance, work by Müller [103,126] proposed the one step mechanism on the basis of several experiments (also supported by Du Bois' studies) [127,128] whereas Dauban has shown some doubts due to the collection of contradictory data: [129] Hammett analyses supported the concerted pathway but KIE studies did not. DFT studies have shown that singlet and triplet states for Rh 2 -II, II -NR are very close in energy [130], and therefore small changes in the catalytic system could influence the reaction pathway.…”
Section: Mechanistic Considerationsmentioning
confidence: 98%